PERBANDINGAN PENDAPATAN USAHATANI PADI SAWAH (Oryza sativa L.) DI DALAM DAN DI LUAR AREAL TAMBANG (Studi Kasus Areal Tambang PT. Multi Harapan Utama di Desa Jonggon Jaya Kecamatan Loa Kulu) (The Income Comparison of Wetland Paddy Farming (Oryza sativa L.) in Inside and Outside of Mining Area (Case Study Mining Area of PT. Multi Harapan Utama in Jonggong Jaya Village Loa Kulu Subdistrict)) - MARKUSDIAN SINAGA; ACHMAD ZAINI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2020)
The purposes of this research were to determine the income of wetland paddy farming in inside and outside of mining area and to compare both of them. This research was conducted from August to October 2018 in minning area of PT. Multi Harapan Utama, Jonggon Jaya Village, Loa Kulu Subdistrict. Data  collection was done through direct interview toward 33 respondents. Data was analyzed to count income and to do t test. The result of this research showed that the average income of wetland paddy farming in inside mining area was IDR12,049,299.99 ha-1 cropping season (cs)-1 while the average income of wetland paddy farming in outside mining area was IDR10,663,654.70 ha-1cs-1. Income of wetland paddy farming in  inside mining area was bigger than that in outside mining area based on tcount > ttable (3.637 > 2.039).